Src and phospho‐FAK kinases are activated by allopregnanolone promoting Schwann cell motility, morphology and myelination. Issue 2 (10th February 2017) - Melfi, Simona; Montt Guevara, Maria Magdalena; Bonalume, Veronica; Ruscica, Massimiliano; Colciago, Alessandra; Simoncini, Tommaso; Magnaghi, Valerio
Abstract: Schwann cells' (SCs) development and maturation require coordinate and complementary activation of several signals and intracellular pathways. Among factors controlling these processes, the signalling intermediates Src tyrosine kinase and focal adhesion kinase (FAK) are relevant for SCs', participating in regulation of their adhesion, motility and migration. Recently, the progesterone metabolite allopregnanolone (ALLO) was proved to be synthesized by SCs, whereas it acts autocrinally on SCs motility and proliferation, which are crucial processes for nerve development, maturation and regeneration. Herein, we investigate the hypothesis that the molecular mechanisms behind the ALLO's action on SCs involve the signalling intermediates Src and FAK. We first demonstrated that ALLO 10 −6 M regulates SCs morphology, motility and myelination, also increasing the internode distance in the in vitro myelination model of neuron/SCs co‐culture. ALLO's actions were mediated by the modulation of Src/FAK pathway, since they were counteracted by PP2 10 −5 M, a selective inhibitor of Src kinase. Then, we proved that Src/FAK activation in SCs involves GABA‐A dependent mechanisms and actin re‐arrangements. In conclusion, our findings are the first to corroborate the importance of the neuroactive steroid ALLO in regulating SCs development and maturation via the Src and phospho‐FAK signalling activation. Cover Image for this issue: doi:10.1111/jnc.13795 . Abstract : We suggest that the progesterone metabolite Allopregnanolone is active in regulating Schwann cells proliferation, motility, morphological rearrangements and myelination. These actions are γ‐amino butyric acid type A receptor (GABA‐A) mediated and involve the activation of Src and phospho‐ focal adhesion kinases (FAK). Cover Image for this issue: doi:10.1111/jnc.13795 .